Silmitasertib plus gemcitabine and cisplatin first‐line therapy in locally advanced/metastatic cholangiocarcinoma: A Phase 1b/2 study. Issue 3 (17th March 2023) - Borad, Mitesh J.; Bai, Li‐Yuan; Richards, Donald; Mody, Kabir; Hubbard, Joleen; Rha, Sun Young; Soong, John; McCormick, Daniel; Tse, Emmett; O'Brien, Daniel; Bayat, Ahmad; Ahn, Daniel; et al.
Abstract : Background and Aims: This study aimed to investigate safety and efficacy of silmitasertib, an oral small molecule casein kinase 2 inhibitor, plus gemcitabine and cisplatin (G+C) versus G+C in locally advanced/metastatic cholangiocarcinoma. Approach and Results: This work is a Phase 1b/2 study (S4‐13‐001). In Phase 2, patients received silmitasertib 1000 mg twice daily for 10 days with G+C on Days 1 and 8 of a 21‐day cycle. Primary efficacy endpoint was progression‐free survival (PFS) in the modified intent‐to‐treat population (defined as patients who completed at least one cycle of silmitasertib without dose interruption/reduction) from both phases (silmitasertib/G+C n = 55, G+C n = 29). The response was assessed by Response Evaluation Criteria in Solid Tumors v1.1. The median PFS was 11.2 months (95% confidence interval [CI], 7.6, 14.7) versus 5.8 months (95% CI, 3.1, not evaluable [NE]) ( p  = 0.0496); 10‐month PFS was 56.1% (95% CI, 38.8%, 70.2%) versus 22.2% (95% CI, 1.8%, 56.7%); and median overall survival was 17.4 months (95% CI, 13.4, 25.7) versus 14.9 months (95% CI, 9.9, NE) with silmitasertib/G+C versus G+C. Overall response rate was 34.0% versus 30.8%; the disease control rate was 86.0% versus 88.5% with silmitasertib/G+C versus G+C. Almost all silmitasertib/G+C (99%) and G+C (93%) patients reported at least one treatment emergent adverse event (TEAE). The most common TEAEs (all grades) with silmitasertib/G+C versus G+C were diarrhea (70% versus 13%), nausea (59% vs. 30%), fatigue (47% vs. 47%), vomiting (39% vs. 7%), and anemia (39% vs. 30%). Twelve patients (10%) discontinued treatment because of TEAEs during the study. Conclusions: Silmitasertib/G+C demonstrated promising preliminary evidence of efficacy for the first‐line treatment of patients with locally advanced/metastatic cholangiocarcinoma. Abstract :